Вплив інноваційної технології оптимізації фізкультурної освіти старших дошкільнят на показники їхньої фізкультурної освіченості й рівень захворюваності - Томенко, Олександр; Tomenko, Alexander; Старченко, Анастасія; Starchenko, Anastasiya (Сумський державний педагогічний університет імені А. С. Макаренка (м. Суми), 2014)
У статті представлено результати впливу інноваційної технології на показники фізкультурної освіченості старших дошкільнят. Дослідження показали, що за допомогою застосування засобів дитячого фітнесу в різних формах фізичного виховання можна розв’язати основні завдання фізкультурної освіти старших дошкільнят: покращити рівень елементарних знань із фізичної культури та життєво важливих рухових умінь і навичок, а також знизити рівень захворюваності. Results of scientific researches show that in Ukraine witness lowering of health level of children, also special attitude is paid to necessity modern contents of preschool education. Basic role is devoted to preschool educational establishments where it is necessary to create conditions for obtaining by children of elementary knowledge on physical culture and vitally important motor skills and habits which make the basis of preschool physical culture education. Leading scientists consider that the problem of optimization of physical culture education among preschool aged children allows the development of innovative methods and technologies, forms and approaches to quality training in junior school. Article deals with the results of influence of innovative technology on values of elementary physical culture knowledge, necessary motor skills and habits, illnesses of 5–6 year old children and level of physical culture scholarship of parents. Performed research shows that using means of children fitness (fit ball gymnastics, animal aerobics, and gaming fitness) in different forms of physical culture education of senior preschoolers: improve level of elementary knowledge on physical culture and vitally important motive skills and habits, lower level of illness and also increase level of physical culture scholarship of parents.
Influence of Innovative Technology of Optimization of Physical Culture Education of Senior Preschoolers on Indicies of Their Physical Culture Scholarship and Illness Level
Keywords: інноваційна технологія; фізкультурна освіта; дитячий фітнес; старші дошкільнята; innovative technology; physical culture education; child fitness; senior preschoolers